Adesão à terapêutica em idosos polimedicados - Geraldo, Inês (2016)
Polypharmacy, consists of the simultaneous and chronic use of different drugs, is frequent in elderly people (age≥ 65 years) and commits the patient's adherence to therapy, necessary to a successfully treatment. Objectives: Review the scientific evidences of adherence to therapy and polypharmacy in elderly, since this age group is more vulnerable to the use of different drugs. Materials and Methods: A review of published studies between 2005 and July 2015 was carried out using the Pubmed, B-on and SciELO databases, to search the following terms: elderly, polypharmacy, multidrug, polymedicated elderly and therapy adherence. Were used as exclusion criteria: age under 65, seniors not polymedicated, studies in other languages than Portuguese or English, studies published before 2005. Of the 31 studies initially selected, 8 were excluded as meeting any of the exclusion criteria and 23 articles were included in the review. Results and Discussion: The aging process is associated to various diseases, contributing to polypharmacy. In fact, more than half of elderly taking four or more drugs daily and this number increase with the age. Other important problem related to polypharmacy in elderly is the therapy adherence. Besides the variations between studies, the authors indicate values of non-adherence between 20 and 60%, which results in a range of health problems arising out of the increasing of adverse effects, drug-drug interactions, being this risk associated to the number of drugs consumed. Conclusion: More than half of elderly are polymedicated, with a considerable proportion of elderly non-adherent to therapy, which is associated with consequent health risks.